Teaching Reading and Writing: A Guidebook for Tutoring and Remediating Students - Johnson, Andrew P. (Rowman & Littlefield Publishers, 2008)
Providing a wealth of simple, research-based strategies for teaching reading and writing, this book is designed for each chapter to be accessible to teachers, tutors, parents, and paraprofessionals. Teaching Reading and Writing demonstrates that effective literacy instruction does not have to be complicated or expensive. Each chapter provides easy-to use techniques and with Internet search terms. This guide presents teaching methods that can be implemented without having to acquire additional books, packages, or other instructional devices. All you need is paper, pencil, books, teacher creativity and imagination, and a desire to help students.